DRUG PROVISION OF HIV INFECTED CRIMINALS IN INSTITUTIONS OF CRIMINAL-EXECUTIVE SYSTEM OF KRASNODAR REGION - I. V. Kalinin; T. I. Kabakova (Фармация и фармакология (Пятигорск), 2017)
The rapid spread of human immunodeficiency virus (HIV) leads not only to loss of health in persons held in penitentiary institutions, but also to an increase in material costs for drug coverage of the infected, causing the deficit in the budget of the Russian Federation.The aim of the study is the investigation of the problems in drug supply of HIV-infected people and to search for their solutions.Materials and methods. The investigation was conducted on the basis of statistic data, medical statements and accounting to reports of the penitentiary medical organization using methods of analysis, documentary observation, grouping and comparison of data.Results and discussion. It has been established that in institutions of the penal system the number of HIV-infected criminals continues to grow rapidly. It has been determined that currently in the criminal-executive system (CES) of Kuban’ only 5 classes of antiretroviral drugs out of the 10 classes represented on the Russian pharmacy market are used. Hereby the greatest number of drugs used in prison medical organization for conducting antiretroviral therapy (ARVT), are classified as “Nucleoside reverse transcriptase inhibitors” and “Protease Inhibitors”, and other classes of art drugs are represented by only one international nonproprietary name (raltegravir, enfuvirtide, etravirine). Drug treatment of socially significant infectious diseases is supplied centrally and completely satisfies regional needs. The structure of suppliers has been identified and determined. In 2016 the main suppliers were Joint-stock companies (JSC) “National Immunobiological Company” and “R-PHARM”. An acute shortage of drugs for opportunistic infections due to insufficient funding has also been determined. The necessity for urgent replacement of material-technical base in prison pharmacies for compliance with the rules of storage of medicines which can ensure their safety was identified. The imperfection of accounting medicines and urgent necessity of the centralization system of personified registration were revealed. Real needs in funding increasing and the establishment of Central pharmacy were identified.Conclusion. The revealed deficiencies indicate a critical need for opening Central pharmacy in the territorial bodies of the criminal-executive system and establishing a centralized system of personified registration of medical property, as well as improving the process of medical record keeping and the increase in funding.